The Apron Shop : Thread and Dead - Book 3 - Penney, Elizabeth (New York, NY : St. Martins Paperbacks, 2020)
Iris Buckley is busier than ever this July, with the towns annual Lobster Festival fast approaching. In just a matter of days her apron shop Ruffles & Bows, will be jam- packed with tourists eager to lay eyes on its world-class collection of aprons and linens--and Iriss inventory is running low. Then, just when all hope seems lost, Iris gets a call from Eleanor Brady, a wealthy, reclusive spinster who just happens to have trunks full of vintage fabrics. Would Iris like to come down to Eleanors cottage estate Shorehaven and have a look? Before long Iris is on the scene--and on the case. Turns out that Eleanor has rented Shorehaven to the handsome, charismatic environmentalist Dr. Lukas de Wilde and his flock of students. What begins as an apron-scouting endeavor soon morphs into a full-blown murder investigation when Dr. de Wildes beautiful young teaching assistant turns up dead. Now its up to Iris--along with her partner-in-love-and- crime Ian Stewart--to unravel the mystery before the Blueberry Cove killer strikes again.
Keywords: Women dressmakers -- Fiction; Aprons -- Fiction; Murder -- Investigation; Fiction; Maine -- Fiction; Cozy mystery fiction